Endoscopic cartilage tympanoplasty: full thickness and partial thickness tragal graft, - Parelkar,Kartik (2020)
Abstract Introduction: Cartilage is the grafting material of choice for certain disorders of the middle ear. The indications for its routine use remain controversial due to the possible detrimental effect on post-operative hearing. Objective: The present study was carried out to report a personal experience with "tragal cartilage shield" tympanoplasty to compare the results, in terms of graft uptake and hearing improvement, of endoscopic cartilage shield technique using either partial thickness or full thickness tragal cartilage for type 1 tympanoplasty and to highlight the tips for single-handed endoscopic ear surgery. Methods: Fifty patients with safe chronic suppurative otitis media, assisted at out-patient department from February 2014 to September 2015 were selected. They were randomly allocated into two groups, 25 patients were included in group A where a full thickness tragal cartilage was used and 25 patients included in group B where a partial thickness tragal cartilage was used. Audiometry was performed 2 months after the surgery in all cases and the patients were followed for one year. Results: Out of the total of 50 patients 39 (78%) had a successful graft take up, amongst these 22 belonged to group A and 17 belonged to the group B. The hearing improvement was similar in both groups. Conclusion: This study reveals that endoscopic tragal cartilage shield tympanoplasty is a reliable technique; with a high degree of graft take and good hearing results, irrespective of the thickness. Furthermore, the tragal cartilage is easily accessible, adaptable, resistant to resorption and single-handed endoscopic ear surgery is minimally invasive, sutureless and provides a panoramic view of the middle ear.